2021
DOI: 10.1021/acs.energyfuels.0c03519
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Performance of Vinyl Lactam-Based Kinetic Hydrate Inhibitor Polymers after Treatment under a Range of Conditions

Abstract: Well-known kinetic hydrate inhibitors (KHIs) such as poly­(N-vinylcaprolactam) (PVCap), poly­(N-vinylpyrrolidone) (PVP), and 1:1 N-vinylcaprolactam:N-vinylpyrrolidone (VCap:VP) copolymer have been subjected to a range of treatments to determine their reliability and whether the treatment conditions could affect the KHI performance, both positively or negatively. This included thermal aging (at varying temperatures, at varying pH, and in monoethylene glycol (MEG) solvent), treatment with microwaves or ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Advanced surface science is a prerequisite for the development of targeted LDHIs. ,, As surface-active reagents, LDHIs adsorb on the surface of ensuing hydrate nuclei and retard their growth and/or aggregation. , This necessitates an insightful understanding of the interaction between LDHI molecules and the hydrate surface. , The attractive force between LDHI molecules and the hydrate surface (i.e., the driving force of LDHIs adsorption) acts within a subnanometer range, meaning that the adsorption process is dictated only by a few outmost water layers of the hydrate surface. Carver et al indicated that this driving force arises from the hydrogen bonding between hydrophilic sites of LDHI molecules and water molecules of the hydrate surface. , This mechanism applies to hydrate surfaces contacting a gas or hydrophobic environment.…”
Section: Applications In Sustainable Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced surface science is a prerequisite for the development of targeted LDHIs. ,, As surface-active reagents, LDHIs adsorb on the surface of ensuing hydrate nuclei and retard their growth and/or aggregation. , This necessitates an insightful understanding of the interaction between LDHI molecules and the hydrate surface. , The attractive force between LDHI molecules and the hydrate surface (i.e., the driving force of LDHIs adsorption) acts within a subnanometer range, meaning that the adsorption process is dictated only by a few outmost water layers of the hydrate surface. Carver et al indicated that this driving force arises from the hydrogen bonding between hydrophilic sites of LDHI molecules and water molecules of the hydrate surface. , This mechanism applies to hydrate surfaces contacting a gas or hydrophobic environment.…”
Section: Applications In Sustainable Technologiesmentioning
confidence: 99%
“…First, the QLL alters the adsorption mechanism, for example, changing from a hydrogen-bonding regime (Figure a) to a hydration regime (Figure b). Second, LDHIs are complex molecules containing functional (hydrophilic/charged) sites. , As such, a rigid solid surface can only contact certain sites of LDHI molecules at one time (Figure c), but a premelting surface can deform to reach a larger number of functional sites (Figure d). The latter leads to an improved driving force of the adsorption.…”
Section: Applications In Sustainable Technologiesmentioning
confidence: 99%
“…We previously found that extreme mechanical stress from ball-milling can reduce the polymer molecular weight to shorter chain lengths. 52 In addition, it was reported that the phosphonation reaction of original chitosan under conventional conditions led to a decrease in its molecular weight. [53][54][55] It is well known that low molecular weight polymers exhibit optimal scale inhibition performance in petroleum industry applications.…”
Section: Chemistrymentioning
confidence: 99%
“…KHIs are water-soluble polymers containing imide or amide functional groups, and they are typically used at 0.1-2 wt.% [21][22][23]. Poly(N-vinyl lactam)s, poly(N-isopropylacrylamide), polyvinylpolypyrrolidone, poly(N-alkyl (meth)acrylamide)s, and hyperbranched polyesteramide are commercially available KHIs [24][25][26]. The mechanism action of KHIs is predominantly on the kinetics of gas hydrate formation by delaying nucleation and crystal growth of hydrates [27][28][29].…”
Section: Introductionmentioning
confidence: 99%